Study on the location of unconventional outside left-turn lane at signalized intersections based on an entropy method - Liu, Xijun; Shao, Chaoyi; Yang, Shuai; Zhang, Ranyang; Pan, Binhong (Frontiers in Environmental Science, 2022)
A good air environment and smooth traffic environment are important for smart city building and sustainable development. However, with the increase of urban population and traffic volume, traditional intersections often face serious congestion problems, which makes vehicle emissions increase greatly and seriously threatens urban air quality. To alleviate this problem, the unconventional design with an outside left turn lane on the right side of the through lanes has been widely used in China. However, there is little research and guidance on the location of unconventional outside left-turn lane settings. Therefore, this paper collects traffic data from a signalized intersection with unconventional outside left-turn lane design in Xi'an, and evaluates and analyzes the outside left-turn lane design at different locations using the entropy weight method (EWM). The simulation of the outside left-turn lane with different setting locations is performed in VISSIM and six indexes are analyzed. Finally, EWM is innovatively used to calculate the weights of the adopted indexes to achieve a comprehensive evaluation of different location schemes under different traffic scenarios. It was found that the differences in vehicle emissions were as high as 54.7% with different locations of the outside left-turn lane design, and the vehicles operated with different efficiencies. The unconventional design with the outside left-turn lane in the sub-outermost lane is suitable for most traffic conditions, while the design with the outside left-turn lane in the outermost lane performs better at high traffic volumes. The conventional outside left turn lane design is suitable for light traffic.